Assessment of rheological methods to study crystallization of palm oil fractions. Issue 2 (20th November 2020) - Tangsanthatkun, Janjira; Wiking, Lars; Sonwai, Sopark; Gregersen, Sandra Beyer
Abstract: This study provides an evaluation of the use of rheology to characterize soft, semi‐hard, and hard fats in relation to determine the crystallization onset, crystallization behavior, as well as microstructure development using either a plate–plate or a starch pasting cell (SPC). The results from this study demonstrate that when applying rheology to study fat crystallization, the results must be interpreted with care. The application of a plate–plate geometry allowed for sensitive evaluation of the initial nucleation phase, which was not possible with an SPC. Both geometries could provide information on crystallization behavior in terms of one‐step or two‐step crystallization. However, in the late stage of the crystallization process, when the fat crystals form a strong network, the SPC could not describe differences in the rheology of the fat‐crystal network, which was a possibility by the use of a plate–plate geometry. Thus, oscillatory rheology with a suitable geometry can be used to evaluate the entire crystallization process.